This study aims to improve the early reading skills of second-grade students at SD Naskat Awear Rumngevur through the use of illustrated word card media. The research was motivated by the students’ low reading ability, as indicated by slow reading process - Marsela Watkaat; Nurhidayati Nurhidayati (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aims to improve the early reading skills of second-grade students at SD Naskat Awear Rumngevur through the use of illustrated word card media. The research was motivated by the students’ low reading ability, as indicated by slow reading processes, difficulties in combining letters into syllables or words, and frequent pronunciation errors. The research employed a Classroom Action Research (CAR) approach based on the Kemmis & McTaggart model, implemented in two cycles with 13 students. Data were collected through observation and early reading skill tests. The results demonstrated a significant improvement in students’ reading skills: the mastery level increased from 51.1% in the first cycle to 82.9% in the second cycle, with the average score rising from “fair” to “very good.” In addition to quantitative gains, there were notable improvements in reading fluency, pronunciation accuracy, intonation, and active participation. These findings confirm that illustrated word card media are effective as an innovative instructional strategy for enhancing early reading skills in elementary school students. The practical implication of this research is the necessity for teachers to develop and utilize simple learning media suited to students’ characteristics.